Diversidade de larvas de peixes em uma área de conservação de uma planície de inundação neotropical : influência de escalas temporais e espaciais. - Silva, Camila Barbosa (2014)
The fish larvae are organisms that exhibit spatial and temporal variations in floodplain environments. In order to evaluate how the diversity of fish larvae are structured in different temporal (months and hours) and spatial (biotopes) scales in the sub-basin of the Ivinheima river (MS), upper Paraná River floodplain, monthly samples of fish larvae were carried out in two reproductive periods. Samplings were conducted in seven stations, which were grouped according to the biotope that they belong (lagoon, river and remanso) and at four different hours of the day. The samples were always collected using a cylindrical-conical plankton net (mesh aperture of 500-μm) and equipped with a mechanical flowmeter. The individuals were sorted and identified. The variation of α diversity was evaluated using a nested ANOVA, and the variation of β diversity was assessed using a dispersion multivariate analysis based on distance (PERMDISP). The additive partitioning was used to verify the relative contribution of each scale to γ diversity. The reproductive period of 2010/2011 (PR1) had the highest intensity in flood and this favored a greater γ diversity of fish larvae due to the increase of β diversity. The α and β diversity also varied among different biotopes, where species with different reproductive strategies occupied different biotopes. Among the hours, there was only variation of α diversity, which was higher at night. The components β1 (variation between months) and β3 (variation between biotopes), significantly explain the γ diversity in both reproductive periods, indicating that the floods with higher intensity may favor the reproduction and thus a greater diversity of fish larvae. Both temporal and spatial scales are important in maintaining the biodiversity of a system. In this sense, it is suggested that conservation efforts should consider not only the space but also prioritize the temporal hydrological dynamics that occurs in rivers, especially in places affected by dams which control the operation of these systems. Eggs and larvae in different stages of development need different environments to complete their life cycle. Thus, the maintenance of heterogeneous areas, that is, with different characteristics, promotes diversity as a whole, because they allow different species to reproduce in this area.